How do primary care clinicians approach the management of frailty? A qualitative interview study - Seeley, A; Glogowska, M; Hayward, G (Oxford University Press, 2024)
Background:Around 15% of adults aged over 65 live with moderate or severe frailty. Contractual requirements for management of frailty are minimal and neither incentivised nor reinforced. Previous research has shown frailty identification in primary care is ad hoc and opportunistic, but there has been little focus on the challenges of frailty management, particularly within the context of recent introduction of primary care networks and an expanding allied health professional workforce. Aim: Explore the views of primary care clinicians in England on the management of frailty. Design and setting: Semi-structured interviews were conducted with clinicians across England, including general practitioners (GPs), physician associates, nurse practitioners, paramedics and clinical pharmacists. Thematic analysis was facilitated through NVivo (Version 12). Results: A total of 31 clinicians participated. Frailty management was viewed as complex and outside of clinical guidelines with medication optimisation highlighted as a key example. Senior clinicians, particularly experienced GPs, were more comfortable with managing risk. Relational care was important in prioritising patient wishes and autonomy, for instance to remain at home despite deteriorations in health. In settings where more formalised multidisciplinary frailty services had been established this was viewed as successful by clinicians involved. Conclusion: Primary care clinicians perceive frailty as best managed through trusted relationships with patients, and with support from experienced clinicians. New multidisciplinary working in primary care could enhance frailty services, but must keep continuity in mind. There is a lack of evidence or guidance for specific interventions or management approaches.